A Cidade em disputa: a trajetória de um movimento social - Gomes, Marília Passos Apoliano (2013)
This research analyzes the experience of residents for the Right to the City and the recognition of the Special Zone of Social Interest (ZEIS) of Lagamar, in Fortaleza. The focus is on mobilizing of residents, especially seen in the conflict between them and the government, as to the effectiveness of public policy priorities in a ZEIS and also as to the realization in the locality of a civil work for the 2014 World Cup. Inquire about what the particularities of this mobilization, including actors, connexions, strategies and challenges they faced. It should be clarified that this is a single case because Lagamar had not been recognized as ZEIS at the Master Plan for Fortaleza in 2009; it was only included in a Supplementary Law approved in 2010, due to pressures from residents. Despite the delay in the inclusion, in Fortaleza Lagamar was the first locality to elect its Management Council, demonstrating the possibility of being the first ZEIS to be implemented in the municipality. Through participant observation methodology, between 2010 and 2013 I witnessed several meetings of the Forum and the Management Council, which are ideal areas for observation and analysis. Interviews were conducted with four residents who participate in these spaces, and with one of the technicians of the city government who participated in the Council in the first administration (2011-2012). In addition, the research considered data collected in the Census Community of Lagamar (2005) and in the IBGE census of 2000 and 2010. Regarding the theoretical framework about social movements, I performed a comparison amons researches conducted by Ruth Cardoso, Evelina Dagnino, Linda Gondim, Irlys Barreira, Ana Maria Doimo, Glory Diógenes, Carlos Nelson Ferreira dos Santos, Daniel Cefai and Jan Bitoun. In the study of the Special Zones of Social Interest, there was a theoretical dialogue with Marcelo Lopes de Souza, Ana Lucia Ancona, Renato Pequeno, Clarissa Freitas, and José Afonso da Silva.